2022
DOI: 10.1177/15269248221087440
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Medication Adherence and Tacrolimus Coefficient of Variation

Abstract: Introduction: High tacrolimus intrapatient variability is associated with poor outcomes following transplantation. A commonly hypothesized cause of this variability is medication non-adherence, but this has not been conclusively demonstrated. Research Question: The purpose of this study was to evaluate the relationship between medication adherence and tacrolimus intrapatient variability. Design: This was a retrospective cohort study of kidney transplant recipients. Adherence was assessed at the 12-month clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…51–54 Once these factors are accounted for, NA’s contribution to blood-level variability is barely discernible. 55 Still, although blood assays provide little useful information on the implementation aspect of adherence, they are considered able to detect aspects our available data did not allow us to check, that is, noninitiation or discontinuation of the medication regime. 1…”
Section: Discussionmentioning
confidence: 90%
“…51–54 Once these factors are accounted for, NA’s contribution to blood-level variability is barely discernible. 55 Still, although blood assays provide little useful information on the implementation aspect of adherence, they are considered able to detect aspects our available data did not allow us to check, that is, noninitiation or discontinuation of the medication regime. 1…”
Section: Discussionmentioning
confidence: 90%
“…However, despite the strong correlation with graft outcomes, intra‐patient tacrolimus variability has not been specifically validated as a measure of adherence. There was no correlation between tacrolimus variability and electronically‐measured medication adherence 34,48,52 nor adherence based on a composite of self‐report, pharmacist report and completion of tacrolimus laboratory monitoring 53 . A prospective observational study in kidney transplant recipients that aimed to assess concordance and accuracy of different adherence measurement methods found no concordance between adherence by tacrolimus CV and adherence by electronic monitoring 34 .…”
Section: Discussionmentioning
confidence: 99%
“…There was no correlation between tacrolimus variability and electronically-measured medication adherence 34,48,52 nor adherence based on a composite of self-report, pharmacist report and completion of tacrolimus laboratory monitoring. 53 A prospective observational study in kidney transplant recipients that aimed to assess concordance and accuracy of different adherence measurement methods found no concordance between adherence by tacrolimus CV and adherence by electronic monitoring. 34 Similarly, randomized controlled trials in adult 52 and adolescent 54 kidney transplant recipients showed better electronically monitored adherence in the intervention than control group but no difference between groups by intra-patient tacrolimus variability.…”
Section: Sex Differences In Adherencementioning
confidence: 99%
“…Undetectable drug levels or high intrapatient variability are often used as surrogates for tacrolimus adherence, but the specificity associated with this approach is low. 111,112 For mycophenolic acid, a small study found that a simulated 95% prediction interval for mycophenolic acid concentration identified most patients as adherent, with only fair agreement with refill records. 113 Regardless, the addition of home-based VAMS may provide some insight, with the assumption that adherence to monitoring suggests medication adherence.…”
Section: Adherencementioning
confidence: 99%